LCCO2 Assessment and Fertilizer Production from Absorbed-CO2 Solid Matter in a Small-Scale DACCU Plant - Tianjiao Cheng; Takeji Hirota; Hiroshi Onoda; Andante Hadi Pandyaswargo (Energies)
This study investigates a novel method of utilizing Direct Air Capture (DAC) technology for fertilizer production. Unlike traditional Direct Air Carbon Capture and Utilization (DACCU) technologies, Direct Air Carbon Capture for Fertilizers (FDAC) has the potential to produce fertilizers directly. This study aims to assess the feasibility of FDAC-based fertilizer production by examining the current state of traditional DAC technologies, evaluating the CO2 fixation potential of FDAC, and analyzing the decarbonization effect of producing fertilizers using FDAC. Our evaluation results indicate that CO2 emissions from producing 1 ton of conventional chemical fertilizer, FDAC fertilizer (current status), FDAC fertilizer with ingredient adjustment (sodium hydroxide), and FDAC fertilizer with ingredient adjustment (magnesium hydroxide) are 1.69, 1.12, 1.04, and 1.06 tons of CO2, respectively. The FDAC fertilizer (current status) emits 0.57 tons of CO2 per ton less than commercial fertilizers. FDAC fertilizers also have the potential to reduce CO2 emissions further when the fertilizer composition is adjusted, offering a promising solution for lowering the environmental impact of fertilizer production. Significant CO2 reduction can be expected by replacing conventional low-intensity chemical fertilizers with FDAC-produced fertilizers.